Prediction of the Vertical Displacement on the Crest of Keban Dam - Kose, Erkan; Tasci, Levent (Research Information Ltd, 2015)
Dams are important engineering structures, therefore dams should be constructed with the rigors of safety in mind. In this paper; the vertical displacement of the crest of Keban Dam in Turkey, is determined using a grey prediction method. The grey prediction method is a method that produces satisfactory results when we do not have enough experience about a system behaviors. The purpose of this study is to examine the effectiveness of the grey prediction method in systems where a limited amount of data is available or known. In this study the Simple Exponential Smoothing (SES) method; a very well-known prediction method is used for comparison. The results from our investigation indicate that the grey prediction method produces better results, more in-keeping with true values.
Keywords: Deformation; Grey System Theory; Grey Prediction; Simple Exponential Smoothing